Energy input-output analysis of rice production in Nigeria. (15th September 2020) - Kosemani, Babajide S.; Bamgboye, A. Isaac
Abstract: Energy input-output assessment for crop production processes is becoming increasingly important due to increased energy demand. Efficient use of energy can help achieve an environmentally, economically and socially viable sustainable crop production system now and for the future in general. This paper explores the energy inputs and consumption patterns for rice production system in Nigeria. Energy related data were collected through field surveys, direct measurements, interview with farmers and structured questionnaires for two growing seasons in nine (9) rice farms, comprising of three small, medium and large farms, respectively. Energy requirement for land preparation, planting, crop maintenance (fertilization and weed control), threshing, and harvesting were calculated using standard equations. The average energy input for rice production in small, medium and large farms were 14813, 14543 and 14067 MJ/ha, respectively, while the average yield obtainable were 6695, 7060 and 7364 kg/ha, respectively. There is a significant difference among the three farm categories in respect to input energy and agronomical managements such as transplanting date and land preparation. Energy input in fertilizer application was the highest with 73.80, 75.11 and 76.90% of the total energy input in small, medium and large farm, respectively. The net energy values were 82733, 88321 and 93226 MJ/ha, respectively. Energy ratio in small, medium and large farms were 6.58, 7.07 and 7.62, respectively. Large farms had better energy efficiency due to better management of energy resources. Minimizing input energy through increased level of mechanisation will boost rice production in Nigeria. Highlights: Energy input-output energy balance was analysed for rice production in Nigeria. Chemical energy input was the major contributor in small, medium and large farms. Total energy input for rice production varied from 14067 to 14813 MJ/ha. Specific energy ranged from 1.92 to 2.22 MJ/kg paddy rice. The energy ratio ranged from 6.58 to 7.62, which suggests efficient use of energy.